Exosomes: Innocent Bystanders or Critical Culprits in Neurodegenerative Diseases - Beatriz, Margarida; Vilaça, Rita; Lopes, Carla (Frontiers in Cell and Developmental Biology, 2021)
Extracellular vesicles (EVs) are nano-sized membrane-enclosed particles released by cells that participate in intercellular communication through the transfer of biologic material. EVs include exosomes that are small vesicles that were initially associated with the disposal of cellular garbage; however, recent findings point toward a function as natural carriers of a wide variety of genetic material and proteins. Indeed, exosomes are vesicle mediators of intercellular communication and maintenance of cellular homeostasis. The role of exosomes in health and age-associated diseases is far from being understood, but recent evidence implicates exosomes as causative players in the spread of neurodegenerative diseases. Cells from the central nervous system (CNS) use exosomes as a strategy not only to eliminate membranes, toxic proteins, and RNA species but also to mediate short and long cell-to-cell communication as carriers of important messengers and signals. The accumulation of protein aggregates is a common pathological hallmark in many neurodegenerative diseases, including Alzheimer’s disease, Parkinson’s disease, Huntington’s disease, amyotrophic lateral sclerosis, and prion diseases. Protein aggregates can be removed and delivered to degradation by the endo-lysosomal pathway or can be incorporated in multivesicular bodies (MVBs) that are further released to the extracellular space as exosomes. Because exosome transport damaged cellular material, this eventually contributes to the spread of pathological misfolded proteins within the brain, thus promoting the neurodegeneration process. In this review, we focus on the role of exosomes in CNS homeostasis, their possible contribution to the development of neurodegenerative diseases, the usefulness of exosome cargo as biomarkers of disease, and the potential benefits of plasma circulating CNS-derived exosomes.